2020
DOI: 10.1177/0020872820904130
|View full text |Cite
|
Sign up to set email alerts
|

Co-creation of social services on the example of social hackathon: The case of Estonia

Abstract: Drawing on three semi-structured focus group interviews with a sample of 14 social hackathon participants in southern Estonia, this article reports the findings of participants’ experiences of the co-creation process in developing new services or innovative solutions to community problems by using a method of social hackathon. In general, hackathon was perceived as a creative and ‘out-of-the-box’ type of approach, a non-traditional way of thinking and an openness to constructing solutions in a new and creative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…The selection of the right technology to use and its effective organization (Process 1–technological infrastructure setup) are at the base of the sustainable process of idea generation. In fact, it creates a platform on which stakeholders can easily find and offer knowledge and meanwhile co-create innovative projects in a non-traditional creative way of thinking (Toros et al , 2020). Second, in line with Troise et al (2021), process 2 (stakeholder selection) and process 3 (awareness creation) revealed the capability of hackathon platform to engage a multitude of users and, in so doing, to generate network effects.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the right technology to use and its effective organization (Process 1–technological infrastructure setup) are at the base of the sustainable process of idea generation. In fact, it creates a platform on which stakeholders can easily find and offer knowledge and meanwhile co-create innovative projects in a non-traditional creative way of thinking (Toros et al , 2020). Second, in line with Troise et al (2021), process 2 (stakeholder selection) and process 3 (awareness creation) revealed the capability of hackathon platform to engage a multitude of users and, in so doing, to generate network effects.…”
Section: Discussionmentioning
confidence: 99%
“…Võru County is a rural area situated in southern Estonia. Hackathons are one of the core methods of the start-up scene for giving a kick-start to ideas guiding them to pre-incubation, incubation and elevation (Toros et al, 2020). The hackathon as a method was developed within the start-up scene.…”
Section: Design Of the Social Entrepreneurship Master's Programmentioning
confidence: 99%
“…Municipalities in rural areas compared to urban areas cannot provide services equally for everyone in the sparsely populated areas. There is a need for alternative solutions and tailor-made services for those user groups whose needs cannot be met with standardised services, such as transportation services and home care for elderly (Toros et al, 2020). According to Eurostat (2015), Estonia ranked well below the EU average in terms of social protection expenditure per capita.…”
Section: Design Of the Social Entrepreneurship Master's Programmentioning
confidence: 99%
“…Desde el punto de vista de su potencialidad, el hackathon social como herramienta "debe ser flexible, sensible y humanista, considerando las necesidades y habilidades de los participantes" (Toros et al, 2020). Es una metodología que permite adquirir rápidamente y con pocos recursos habilidades de emprendimiento y confianza en los estudiantes (Szymanska, 2020).…”
Section: Sánchezunclassified